Új szempontok Szenci Molnár Albert Psalteriuma metszeteinek értelmezéséhez - Imre, Mihály (Studia Litteraria, 2026)
Albert Szenci Molnár’s psalm book published in Herborn in 1607 is decorated with engraved illustrations, yet researchers of Szenci Molnár’s works so far have not examined these works, which also merit attention as this is the only edition of Psalterion that contains these illustrations. Szenci Molnár wanted his psalm book to fit into the intellectual environment of Germany; however, Rabe, the publishing house, gave him the opportunity to integrate the iconographic traditions into that context. Examples for that are the engraved illustrations of the pelican and the two horsemen, both of which were part of the publishing practice of Georg Rabe and Christoph Rabe; however, they were much more common in books published by Georg Rabe. The engravings, together with their textual descriptions, played a role in shapingSzenci Molnár’s identity as an author, particularly through their connection to the ethos of princely dedications, and to the construction of his heroic role as defender of the faith.